Power Injection on Single Phase Grid System - Ismail, Fauzan; Effendi, Asnal; witrionanda, witrionanda (Faculty of Engineering, Universitas Tanjungpura, 2019)
This paper deals with power injection on single phase grid connected inverter. The simple method is introduced to understand the concept of grid connected systems. A phase Lock Loop (PLL) method estimates the phase-angle of grid system. The output of PLL is used to defines Iref , and the current of inverter becomes a feedback (IL). Both current are derived to produce PWM using current mode controller method. As long as the grid system on fault condition like voltage distortion, therefore the single-phase inverter that connected into the grid should change the role and keep stabilization. The voltages sag and swell are the possible conditions that occurred on a power system. Voltage Sag is an event where the line voltage decreases from the nominal line-voltage for a short period of time. Voltage swell is the event when the line voltage increase from the nominal line voltage. By using PSIM software, the injection and absorption of power into a grid system is verified during a voltage sag, swell, and normal. The simulation shows voltage grid vg, current inverter iinv, current grid, active power P, reactive power Q. The waveform of the measured parameter is analized to define the role of inverter toward grid. the The result shows performance of the proposed inverter to absorb reactive power during swell, and inject reactive power when sagging.Â